Rebel Salvation : Pardon and Amnesty of Confederates in Tennessee - Liulevicius, Kathleen Zebley (Book collections on Project MUSE., 2021)
"Kathleen Liulevicius's 'Rebel Salvation' provides an in-depth look at the process of Reconstruction in Tennessee by using the unique documentary resource of pardon petitions from former Confederate soldiers and sympathizers. In doing so, she reveals the dynamics at work between multiple parties: former rebels, Unionists, Governor William G. Brownlow, and the U.S. Army officers responsible for ushering the state back into the Union. Since most pardon applicants wrote their petitions in 1865 and 1866, these letters vividly reveal the reality of the politically and emotionally charged immediate post-Civil War environment in Tennessee. Not only were the wealthy and the former political and military elite forced to sue for pardon, but also many otherwise ordinary Tennesseans who had in any way supported the Confederacy by performing a civic function or expressing pro-Confederate sentiments. All had to request pardon and amnesty from the President of the United States to regain the right to vote, hold office, practice law, operate a business, and buy and sell land. ... In their applications, former Confederates shaped narratives about the motivating factors prodding them to side with the Confederacy, chronicled their alleged actions during the Civil War, expressed repentance, and pledged to return allegiance to the Federal Union and obey the Constitution. ... a wealth of information about Tennesseans from an array of social and economic backgrounds and include[s] details about many residents who would otherwise be absent from the historical record. ... Since President Johnson wanted the opinion of each state governor as to the suitability of granting a pardon, Tennessee Governor Brownlow read each pardon petition, letters of recommendation, and commented on each file before forwarding the papers to Washington. 'Rebel Salvation' shows that peace would have to grow organically in Tennessee's formerly divided communities with the pardoning of former Confederates becoming a communal process in which neighbors, acquaintances, and the state's governor urged or discouraged President Johnson's clemency"--